Is There an Association between Bell Palsy in Pediatric Patients and COVID-19? - Mohamed E. El-Deeb; Saad Elzayat; Abeer Salamah; Ali Gamal; Shimaa Elgamal; Ahmed El-Sobki (International Archives of Otorhinolaryngology)
Introduction Bell palsy (BP) is an acquired, idiopathic facial palsy linked to lower motor neuron malfunction of the seventh cranial nerve. Several studies have identified BP as one of the many neuropathies that coronavirus disease 2019 (COVID-19) patients have developed, while other studies disagree.